Timepass: youth, class and the politics of waiting in India - Jeffrey, Craig (Delhi, 2010)
Social and economic changes around the globe have propelled increasing numbers of people into situations of chronic waiting, where promised access to political freedoms, social goods, or economic resources is delayed, often indefinitely.
Keywords: College students-Political activity